Ok, well first you want to expand each part.
(3y+4)^2 = (3y+4)(3y+4) = (9y^2 + 24y + 16) [Using FOIL -> multiply first, outer, inner then last)
9(y+1)^2 = 9(y+1)(y+1) = 9(y^2 + 2y +1) = 9y^2 + 18y + 9
Combine like terms...
9y^2 + 24y + 16 - 9y^2 - 18y - 9 = 6y + 7
Now solve for y...
6y + 7 = 79
6y = 72
y = 12
To double check...
(3(12) + 4)^2 - 9((12)+1)^2 = 79
(40)^2 - 9(13)^2 = 79
1600 - 1521 = 79
79 = 79
So y = 12.
2007-05-30 09:37:10
·
answer #1
·
answered by msam17 2
·
1⤊
0⤋
(3y + 4)^2 - 9(y + 1)^2 = 79
Rewriting
(3y + 4)(3y + 4) -9(y+1)(y+1) = 79
Multiplying, or using the "Distributive Property" gives
3y(3y) + 3y(4) + 4(3y) + 4(4) -9(y^2 +y(1) + 1(y) + 1(1)) = 79
Multiplying and adding similar terms gives
9y^2 +12y + 12y + 16 - 9(y^2 +2y + 1) = 79
Multiplying, and adding similar terms gives
9y^2 + 24y + 16 -9y^2 -18y -9 = 79
Adding similar terms gives
6y + 7 = 79
Subtractinng 7 from both sides gives
6y = 72
Diving by 6 on both sides gives
Answer: y = 12
2007-05-30 09:44:16
·
answer #2
·
answered by chavodel93550 3
·
0⤊
0⤋
(3y + 4)^2 - 9(y + 1)^2 = 79
9y^2 + 24y + 16 - 9(y^2 + 2y + 1) = 79
9y^2 + 24y + 16 - 9y^2 - 18y - 9 = 79
24y + 16 - 18y - 9 = 79 [9y^2 gets cancelled]
6y + 7 = 79
6y = 79 - 7 = 72
y = 72/6 = 12
Formula: (a + b)^2 = a^2 + 2ab + b^2
Firstly, in (3y + 4)^2, a = 3y and b = 4.
So, (3y + 4)^2
= (3y)^2 + 2(3y)(4) + 4^2
= 9y^2 + 24y + 16
Next, a = y, b = 1.
So, (y + 1)^2 = y^2 + 2y + 1
2007-05-30 09:31:03
·
answer #3
·
answered by psbhowmick 6
·
1⤊
1⤋
(3y+4)(3y+4) - 9[(y+1)(y+1)] = 79
9y"+24y+16 - 9(y"+2y+1) = 79
9y"+24y+16 - 9y"-18y-9 = 79
6y+7 = 79
6y = 72
y = 12
Although the above answer of -12 was achieved incorrectly, it is also a possible answer. Because when you square y you will achieve a possitive number no matter what.
2007-05-30 09:40:34
·
answer #4
·
answered by SWSprWmn 1
·
0⤊
0⤋
(3y+4)^2 - 9(y+1)^2 = 79
(3y+4)(3y+4) - 9(y+1)(y+1) = 79
9y^2 + 12y + 12y + 16 - 9(y^2 + y + y + 1) = 79
9y^2 + 24y + 16 - 9(y^2 + 2y + 1) = 79
9y^2 + 24y + 16 - 9y^2 + 18y + 9 = 79
9y^2 + 24y + 16 + -9y^2 + 18y + 9 = 79
9y^2 + -9y^2 + 24y + 18y + 16 + 9 = 79
24y + 18y + 16 + 9 = 79
42y + 16 + 9 = 79
42y + 25 = 79
42y = 54
y = 54/42
2007-05-30 09:35:11
·
answer #5
·
answered by Josh 5
·
1⤊
2⤋
(9y^2 + 24y + 16) - 9(y^2 + 2y + 1) = 79
9y^2 + 24y + 16 - 9y^2 - 18y - 9) = 79
6y + 7 = 79
6y = 72
y = 12
2007-05-30 09:36:01
·
answer #6
·
answered by TychaBrahe 7
·
2⤊
0⤋
multiply it out:
9y'' + 24y + 16 - 9y'' - 18y - 9 = 79
6y + 7 = 79
6y = 72
y = 72/6 = 36/3 = 12
2007-05-30 09:32:40
·
answer #7
·
answered by Kerynella 2
·
1⤊
1⤋